Análisis de los modelos de internacionalización de las pymes en el sector software de Colombia en el marco del TLC con Estados Unidos (2018)
Nowadays, the internationalization of SMEs in the software sector is a strategic goal, established as a state policy in the last 11 years promoted by the Colombian government. Due to the global perspective, this industry is considered a "World Class Sector". however, the results obtained are not the projected minimums. It has identified some barriers that do not allow the industry to take off in a competitive manner, these are: the lack of organizational structure of SMEs, poor processes and inadequate customer service, lack of strategic alliances and associativity, no investment in research, development and innovation.